2022
DOI: 10.1016/j.heliyon.2022.e08864
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in Egypt: epidemiology, clinical characterization and bioinformatics analysis

Abstract: COVID-19 is an infectious disease caused by SARS-CoV-2 and has spread globally, resulting in the ongoing coronavirus pandemic. The current study aimed to analyze the clinical and epidemiological features of COVID-19 in Egypt. Oropharyngeal swabs were collected from 197 suspected patients who were admitted to the Army Hospital and confirmation of the positivity was performed by rRT-PCR assay. Whole genomic sequencing was conducted using Illumina iSeq 100® System. The average age of the participants was 48 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(62 reference statements)
3
2
0
Order By: Relevance
“…Our findings regarding the whole genome sequencing of SARS-CoV-2 recovered in 2020 showed that all strains belong to the 20A clade and were mutated and carried D614G, V5F, Q57H and G823S mutations. In agreement with this finding, several studies conducted to track the distribution of viral clades in Egypt reported the higher prevalence of all clades with D614G mutation in 2020 ( Hamed et al, 2021 ; Alotaibi et al, 2022 ; Zekri et al, 2021 ; Kandeil et al, 2020 ). Two isolates were recovered from COVID-19 patients, in September 2021, (accession codes: EPI_ISL_4748272 and EPI_ISL_4748283) were AY.119.2 and AY.44 Pango Lineage, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our findings regarding the whole genome sequencing of SARS-CoV-2 recovered in 2020 showed that all strains belong to the 20A clade and were mutated and carried D614G, V5F, Q57H and G823S mutations. In agreement with this finding, several studies conducted to track the distribution of viral clades in Egypt reported the higher prevalence of all clades with D614G mutation in 2020 ( Hamed et al, 2021 ; Alotaibi et al, 2022 ; Zekri et al, 2021 ; Kandeil et al, 2020 ). Two isolates were recovered from COVID-19 patients, in September 2021, (accession codes: EPI_ISL_4748272 and EPI_ISL_4748283) were AY.119.2 and AY.44 Pango Lineage, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In 2020, 144 Egyptian SARS-CoV-2 isolates were found to have at least 99% identity to the reference strain Wuhan-Hu-1 and exhibited a distinct mutation pattern (D614G/Q57H/V5F/G823S) ( Seadawy et al, 2022 ). During the second wave of the pandemic, the genomic sequences of SARS-CoV-2 were dramatically changed, resulting in several variants that were assigned as variants of concern (VOC) according to the WHO ( Alotaibi et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that fever, fatigue, and cough were the predominant symptoms, while sore throat, loss of taste, anosmia, and GIT symptoms were reported but with less frequency. These observations are in line with the findings of previous investigations (Doghish et al, 2021;Ibrahim et al, 2021;Alotaibi et al, 2022b;Cascella et al, 2022).…”
Section: Discussionsupporting
confidence: 94%
“…We observed that males (75.6%) were more susceptible to COVID-19 infection than females (24.4%), with an approximate mean age of 37. This was in accordance with previous research conducted in Egypt during the first and second waves of COVID-19, which reported that those aged 40 to 60 were the most frequently infected ( AboKresha et al, 2021 ; Alotaibi et al, 2022b ). Furthermore, we recorded each patient’s clinical manifestations in order to contribute to the development of a more clear and comprehensive clinical presentation of COVID-19, which is still unclear due to the SARS-CoV-2 high mutational rate.…”
Section: Discussionsupporting
confidence: 93%
“…Egypt had an endemic level of about 150-200 cases per day until November 2020, with death around 15-25 per day until December, when locally sourced SARS-CoV-2 mutations exhibited at least 99% identity with the Wuhan strain (12). Following this, the number of cases and deaths increased, with a subsequent biphasic trend.…”
Section: Clinical Epidemiologymentioning
confidence: 99%